A promising hypothesis of c-KIT methylation/ expression paradox in c-KIT (+) squamous cell carcinoma of uterine cervix ----- CTCF transcriptional repressor regulates c-KIT proto-oncogene expression. Issue 1 (December 2015) - Chang, Shih-Wen; Chao, Wan-Ru; Ruan, Alexandra; Wang, Po-Hui; Lin, Jau-Chen; Han, Chih-Ping
Abstract We recently reported one interesting case showing mutation-freec-KIT proto-oncogene overexpression and paradoxical hypermethylation in 54 cases of primary squamous cell carcinoma of uterine cervix (SCC). However, its molecular mechanisms still remain unknown. We propose the hypothesis that increased methylation at the CpG islands on the promoter near the first exon region might interfere with the binding of CTCF repressor withc-KIT promoter that regulatesc-KIT proto-oncogene expression in such case. Further studies focusing on the status of epigenetic modifications of mutation-free c-KIT (+) tumors are encouraged.